Clarifying the role of Ru in methanol oxidation at Rucore@Ptshell nanoparticles. Issue 41 (1st October 2015) - El Sawy, Ehab N.; El-Sayed, Hany A.; Birss, Viola I.
Abstract : Rucore @Ptshell NPs with a controlled Ptshell coverage and two different Rucore sizes (2 and 3 nm) were synthesized to determine the precise role of Ru in the MOR activity at Rucore @Ptshell NPs. Abstract : The catalytic activity of Rucore @Ptshell nanoparticles (NPs) towards CO oxidation, a strongly adsorbed intermediate that compromises the performance of direct methanol fuel cells, is known to be significantly better than at Pt alone. However, a systematic study aimed at understanding the beneficial effect of Ru on Pt during the methanol oxidation reaction (MOR) has not been carried out as yet. Here, Rucore @Ptshell NPs, having a controlled Ptshell coverage of zero to two monolayers and two different Rucore sizes (2 and 3 nm), were synthesized using the simple polyol method to determine the precise role and impact of Ru on the MOR in 0.5 M H2 SO4 + 1 M methanol at RT and 60 °C. Because the structure of our Rucore @Ptshell NPs is known with such certainty, we were able to show here that the rate of methanol adsorption/dehydrogenation can be accelerated either by compression of the Ptshell (by making the Rucore larger) when it is less than one monolayer in thickness, or by decreasing the electronic effect of the Rucore on the Ptshell (achieved by adding a second Pt layer to the Ptshell ). At low overpotentials, decreasing the Ptshell thickness also helps in increasing the rate of the MOR by enhancing the rate of oxidation of adsorbed CO. Finally, it is shown that the bi-functional effect of Ru on the Ptshell plays only a minor role in the catalysis of the MOR, especially at large particles where CO surface diffusion is facilitated.